Corpora amylacea and molluscum contagiosum on a cervical pap smear. Issue 2 (8th November 2016) - Buckley, Kaila; Li, Zaibo
Abstract : When evaluating a Papanicolaou (Pap) smear, the cytology of the squamous epithelial cells is of utmost importance. This is what cytopathologists use to render a diagnosis, ranging from normal to atypical squamous cells of undetermined significance (ASCUS) to high grade squamous intraepithelial lesions, or even squamous cell carcinoma. However, occasionally the pathologist will run into microscopic noncellular material as in our case, such as corpora amylacea on the slides, or even uncommon viral inclusions such as Molluscum contagiosum (MCV). When these less common entities make their way on to a cervical Pap smear, it is important not only to correctly recognize them, but to understand their clinical implications as well. Diagn. Cytopathol. 2017;45:179–181. © 2016 Wiley Periodicals, Inc.